DOI: 10.15368/theses.2010.190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium chloride addition during diafiltration on the solubility of milk protein concentrate

Abstract: There is considerable interest among food manufacturers to incorporate protein into food products in both developed and developing countries. Dairy proteins are excellent choices for many different applications, as they are known to have several nutritional and functional benefits. Membrane filtration techniques are often utilized as the preferred method of fractionation, due to the high throughput and continuous nature of the process. One such product produced from membrane filtration of skim milk is called m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…It would therefore appear that minerals affect the protein aggregation and hence the solubility. This was also in agreement to other findings by Gualco (2010) and Havea (2006). Even after production, salts addition would definitely affect solubility as Hussein et al (2011) found out that total rehydration time in native micellar casein was reduced from 467 min to about 217 min and 187 min when NaCl (12% concentration) and CaCl 2 (2.25% concentration) were added, respectively.…”
Section: Causes Of Low Solubility In Mpcsupporting
confidence: 90%
“…It would therefore appear that minerals affect the protein aggregation and hence the solubility. This was also in agreement to other findings by Gualco (2010) and Havea (2006). Even after production, salts addition would definitely affect solubility as Hussein et al (2011) found out that total rehydration time in native micellar casein was reduced from 467 min to about 217 min and 187 min when NaCl (12% concentration) and CaCl 2 (2.25% concentration) were added, respectively.…”
Section: Causes Of Low Solubility In Mpcsupporting
confidence: 90%
“…MPC80 powders were manufactured as described by Gualco (2010). Pasteurized skim milk (140 kg) was ultrafiltered by using a model R12 cross flow membrane recirculatory pilot plant unit (Niro Inc, Hudson, WI, USA) equipped with dual 10 kDa cut-off spiral-wound polyethersulfone membranes (Snyder Filtration, Vacaville, CA, USA).…”
Section: Samples Preparationmentioning
confidence: 99%
“…Replacement of approximately 30% of the calcium of the ultrafiltered skim milk retentate by sodium ions can result in a MPC80 powder with little insoluble material, because removal of calcium ions increases the electrostatic repulsive forces between the casein micelles, to improve hydration properties of MPC80 powder (Havea, 2006). Compared with that of MPC80 powder made without addition of NaCl, the solubility of MPC80 powder produced with NaCl addition during diafiltration increases significantly (Gualco, 2010). The mechanism behind this effect needs further elaboration.…”
Section: Introductionmentioning
confidence: 99%